Dark matter eaudiobook A novel. - Crouch, Blake (Random House Audio, 2016)
NEW YORK TIMES BESTSELLER • OVER ONE MILLION COPIES SOLD! • NOW STREAMING ON APPLE TV+ A “mind-blowing” ( Entertainment Weekly ) speculative thriller about an ordinary man who awakens in a world inexplicably different from the reality he thought he knew—from the author of Upgrade, Recursion, and the Wayward Pines trilogy “Are you happy with your life?” Those are the last words Jason Dessen hears before the kidnapper knocks him unconscious.  Before he awakens to find himself strapped to a gurney, surrounded by strangers in hazmat suits. Before a man he’s never met smiles down at him and says, “Welcome back, my friend.” In this world he’s woken up to, Jason’s life is not the one he knows. His wife is not his wife. His son was never born. And Jason is not an ordinary college professor but a celebrated genius who has achieved something remarkable. Something impossible. Is it this life or the other that’s the dream? And even if the home he remembers is real, how will Jason make it back to the family he loves? From the bestselling author Blake Crouch, Dark Matter is a mind-bending thriller about choices, paths not taken, and how far we’ll go to claim the lives we dream of.